Epifania twarzy czy iluzja maski? O zmaganiu się człowieka w ujęciu filozofii dramatu Józefa Tischnera - Mizdrak, Inga (Przestrzenie Teorii, 2021)
The aim of the article is to present human issues in the context of the face and the mask as its negative. This is to bring us closer to a better diagnosis of the human condition today and the changes that can be articulated on its basis. Both the face and the mask are multi-context, and any attempt to define them encounters a number of difficulties. In Józef Tischner’s philosophy of drama, the face is a condition for the essence of the meeting. On the other hand, the mask, as an appearance and falsification of the truth of the face, is placed in the ambiguous perspective of hiding, concealing, mystifying or obscuring or obscuring the image of the face. Thanks to the face, man is somehow “at home”, and in the bonds of the mask he is somewhat “out of place”, he is lying. The face is relational and the mask is reactionary. Inquiries about whether the face brings closer and reveals the naked being of a human intensified questions about the nature of the face itself and whether it is possible to reach the pure phenomenon of the face as such. Both the face and the mask reveal important moments in the characteristics of a human being as a dramatic being, in which questions about meaning, identity, freedom and responsibility, as well as what is “between” I and You, gain in intensity and imply new attempts to reveal who is a human.